Epidemiological aspects thyroid cancer - El Ters, Escandor; Delgado, Bolívar (Cirugía del Uruguay, 1996)
The authors analyse the íncídence of thyroid cancer in the city of Montevideo and morta!ity in Uruguay between 1988 and 1992, pointíng out that whi/e the former increases, the latter decreases, confirming the existence of better diagnosis and treatment of this patho/ogy andlor /ess malignancy in thyroid cancer evolutioti. The analysís of the personal casuístry of one of the authors (B. Delgado) in the case of dífferentiated cancer of the thyroíd shows a predominancy in fema/es, young and middle aged patíents, and thyroid nodule as c/ínícal presentation. From the hístologica/ poínt of víew, papillary carcinoma predomina/es; an importan/ percentage with cervical nades. Our country has the profí/e of an endemícal zone for goiter wíth a higher incídence of follicular carcinomas when compared to non-endemica/ zones ar endemícal ones with addítíonal iodíne intake